Respuesta de la paprika capsicum annuum l. variedad longum a la fertilización química a base de n-p-k en la granja Santa Inés - Pacheco Valarezo, Cristhian Hernan (2013)
The present research objective is to show the response or reaction of paprika (Capsicum annuum L) the same that belongs to the logum variety of plants to the chemical fertilization made besed on the N-P-K in Santa Ines it was carried out in the Agronomy Faculty of the Technical University of Machala, during the time period of June-October 2013 these research objectives include: 1. To determine the reaction or response of paprika to the chemical fertilizers based on the concentration of N-P-K components. To know the appropriate doses to get the best results during the agronomical plants production. 3 to determine an economical analisis of using this kind of chemical components, in this case were used non certified seeds, insecticides, fungicides, and the technique used to water plants was by sprinkler system irrigation, for fertilization were used 46 percent of Urea, diammonium phosphate 46 percent of P2O5, 60 percent of muriaticum-potassium of K2O, the levels of fertilizers were as recommended 240-140-260 kg de N, P2O5, K2O for the zone of Piura-Peru and these were T1. 320-2290-340; T2.280-180-300; T3. 240-140-260; T4. 200-100-220; T5. 160-60-180 de N-P-K. T6 0-0-0 de N-P-K. Among other conditions and agronomical variants were considered the height 30, 60, 90, the number stated per plant of fruit or product, other conditions were the weight, diameter and length of plant product and the last one was the proper value in return per hectare of the cultivated land. The experimental desing was applied on blocks of land taken at random including six treatments and four repetitive rounds or replications. Concluding with a total of 24 experimental units. The agro-ecological production of paprika in Santa Ines yield kept the average level of production per hectare. The results differ from those obtained in Peru in part because the non-certified paprika seeds used during this experimental research. The best results obtained in terms benefit-cost was the T3. 240-140-260 of N-P-K applying as a primary resource, the macro elements urea, ammonium phosphate and muriate potassium